Perbedaan Quality of Life Lansia Hipertensi yang Mengikuti dan Tidak Mengikuti Senam Prolanis di Wilayah Benteng Kota Ambon - Manuhutu, Adita Ayu Ferdinansih; Prasetya, Berta Esti Ari (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2018)
This study aims to determine differences in Quality of Life. This study was carried out on 70 people, namely elderly hypertension who followed prolanist gymnastic as many as 35 people and elderly hypertension who did not follow prolanist gymnastics as many as 35 people, using purposive sampling technique. Data collection was carried out using the World Health Organization Quality of Life (Whoqol) -Bref Scale. Data analysis method uses t-test analysis. The results of data analysis using the t-test yielded a t-count value of 4.665 with a significance of 0.000 (p <0.05) and a standard deviation of 9,595. There is a significant difference between the quality of life of elderly hypertension who follow prolanist gymnastics and elderly hypertension who do not follow prolanist gymnastics in Benteng Region, Ambon City.